2008
DOI: 10.1152/ajprenal.90228.2008
|View full text |Cite
|
Sign up to set email alerts
|

Urea transporters UT-A1 and UT-A3 accumulate in the plasma membrane in response to increased hypertonicity

Abstract: Blessing NW, Blount MA, Sands JM, Martin CF, Klein JD. Urea transporters UT-A1 and UT-A3 accumulate in the plasma membrane in response to increased hypertonicity. Am J Physiol Renal Physiol 295: F1336 -F1341, 2008. First published August 20, 2008 doi:10.1152/ajprenal.90228.2008.-The UT-A1 and UT-A3 urea transporters are expressed in the terminal inner medullary collecting duct (IMCD) and play an important role in the production of concentrated urine. We showed that both hyperosmolarity and vasopressin increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Thus, we speculate that this increase is to compensate for the reduced concentrating ability in the diabetic kidney. Likewise, as UT-A2 and UT-B compensate for the action of the each other, the increase observed in UT-B and thereby a decrease in UT-A2 may result from a challenge to restore inner medullary interstitial urea, which is disrupted even in the early stage of diabetes (11,13,15). Although changes are observed both in urea gradient and urea transporter expression, the NGAL marker included in this study indicated that no kidney injury can be seen in the early stages of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculate that this increase is to compensate for the reduced concentrating ability in the diabetic kidney. Likewise, as UT-A2 and UT-B compensate for the action of the each other, the increase observed in UT-B and thereby a decrease in UT-A2 may result from a challenge to restore inner medullary interstitial urea, which is disrupted even in the early stage of diabetes (11,13,15). Although changes are observed both in urea gradient and urea transporter expression, the NGAL marker included in this study indicated that no kidney injury can be seen in the early stages of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Vasopressin and hyperosmolality have an additive stimulatory effect on urea permeability (11,16,17). Hyperosmolality, similar to vasopressin, increases the phosphorylation and the plasma membrane accumulation of both UT-A1 and UT-A3 (14,26,32,33). However, hyperosmolality and vasopressin signal through different pathways: hyperosmolality via increases in protein kinase Ca and Figure 6.…”
Section: Rapid Regulation Of Urea Transporter Proteinsmentioning
confidence: 99%
“…Then, cells were treated with hyperosmolar solutions containing 550 or 800 mOsm/kg H 2 O for 1 h. Medium components used in acute adaptation were 250 mOsm/kg H 2 O (125 mmol/l) NaCl, 250 mOsm/kg H 2 O (250 mmol/l) urea, or 125 mOsm/kg H 2 O (62.5 mmol/l) NaCl plus 125 mOsm/kg H 2 O (125 mmol/l) urea, by adding the desired volume of solute stock solutions of 2.5 mol/l NaCl or 5 mol/l urea prepared in iso medium and filter sterilized. For hypertonic stimulation and release experiments, cells were stimulated with 800 mOsm/kg H 2 O NaCl plus urea for 1 h to redistribute UT-A1 and then cells were cultured in iso medium for 2 h to allow recovery [1]. Cells were then harvested after treatment for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Biotinylation of the cell surface was carried out with the Pierce Cell Surface Protein Isolation kit (Pierce) following the manufacturer's instructions [1,12]. At the desired times after treatment, cell surface proteins were labeled with sulfosuccinimidyl-2-(biotinamido)ethyl-1,3-dithiopropionate (Sulfo-NHS-SS-biotin; Pierce).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation